THE ROLE OF COMPENSATION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE: A LITERATURE REVIEW ON COMPANIES IN INDONESIA - Nabila Apriliani; Hubbansyah, Aulia Keiko (INQUISITIVE : International Journal of Economic, 2024)
The purpose of this research is to analyze how compensation and work motivation influence employee performance within the framework of Human Resource Management (HRM). This article utilizes a literature review method to explore relevant information. Data were collected from Google Scholar, spanning the period from 2015 to 2024. The results of the analysis indicate that compensation and work motivation have a positive and significant influence and play an important role in improving employee performance. However, non-financial compensation that does not meet needs can have negative impacts, as well as the lack of work motivation provided by the company. In conclusion, throughout this literature research, the findings indicate that compensation and work motivation have a positive and significant influence and play an important role in improving employee performance. Enhancing the role of compensation and work motivation in the performance of company employees is a key factor in motivating and retaining the best talents, as well as improving overall organizational productivity.